Evaluating the efficacy of Dfrag tablets on human sperm DNA fragmentation - insights from a prospective clinical study - Raj, Mala; J., Roobini; Kasturiraj, Aarathy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Infertility affects approximately 8-10% of couples worldwide. Sperm deoxyribonucleic acid (DNA) fragmentation index (DFI) has emerged as a significant factor in infertility research, highlighting its importance in understanding reproductive health. Methods: This prospective clinical study aimed to assess the impact of Dfrag® tablets, a unique nutraceutical combination containing vitamin D3 (600 IU), selenomethionine (40 mcg), coenzyme Q10 (100 mg), and astaxanthin (8 mg), on high sperm DFI over a 3-month period. The study utilized the sperm chromatin dispersion test (SCD) to measure DFI and examined semen parameters before and after the intervention. Results: Dfrag® tablets were found to significantly improve semen volume, total sperm count, sperm concentration, and progressive motility within the 3-month treatment period. The study reported an average reduction of 36% in DNA fragmentation levels post-treatment with Dfrag® tablets. However, no significant changes were observed in total motility or sperm morphology. Conclusions: This study demonstrates the potential of Dfrag® tablets in reducing sperm DNA fragmentation and improving key semen parameters associated with fertility.